Hydrogen in Nickel: Hydride or Miscibility Gap? - Movchan, D.N.; Teus, S.M.; Mogilny, G.S.; Gavriljuk, V.G. (Металлофизика и новейшие технологии, 2013)
Using low temperature X-ray diffraction, the phase transformations in the hydrogen-saturated nickel are studied. At the hydrogen degassing, its content in nickel decreases down to H/M ratio of about 0.65. The further decreasing of hydrogen content leads to the two-phase separation, notably, hydrogen-rich and hydrogen-depleted solid solutions with permanent hydrogen concentrations existing while the hydrogen-rich phase does not disappear. Based on the Gibbs’ idea about two types of precipitation reactions and available experimental data, it is concluded that, in fact, the so-called Ni-hydride is a hydrogen-rich solid solution, which appears because of miscibility gap in the Ni—H system. At higher hydrogen contents beyond the crown, hydrogenrich phase exists in the wide concentration range as a supersaturated hydrogen solid solution in nickel, which is also incorrectly interpreted as Nihydride. За допомогою низькотемпературної Рентґенової дифрактометрії було досліджено фазові перетворення в насиченому воднем нікелі. Було визначено, що при дегазації водню його вміст у нікелі зменшується до співвідношення Н/Ме, близького до 0,65. Подальше зменшення вмісту водню призводить до поділу на дві фази – збагачений воднем і збіднений воднем тверді розчини, що містять незмінну кількість водню аж до зникнення збагаченої воднем фази. Спираючись на ідею Ґіббса щодо двох типів реакцій утворення і наявні експериментальні дані, зроблено висновок, що насправді так званий гідрид нікелю є твердим розчином водню в нікелі, який виникає внаслідок розриву змішуваності в системі Ni—H. При подальшому збільшенні вмісту водню за межами купола він існує в широкому інтервалі концентрацій як перенасичений твердий розчин водню в нікелі, котрий некоректно інтерпретують як гідрид нікелю. Посредством низкотемпературной рентгеновской дифрактометрии были исследованы фазовые превращения в насыщенном водородом никеле. Было определено, что при дегазации водорода его содержание в никеле уменьшается до соотношения Н/Ме около 0,65. Дальнейшее уменьшение содержания водорода приводит к разделению на две фазы – обогащённый водородом и обеднённый водородом твёрдые растворы, содержащие неизменное количество водорода вплоть до исчезновения обогащённой водородом фазы. Опираясь на идею Гиббса о двух типах реакций выделения и существующие экспериментальные данные, сделан вывод, что в действительности так называемый гидрид никеля является твёрдым раствором водорода в никеле, образующимся в результате разрыва смешиваемости в системе Ni—H. При дальнейшем увеличении содержания водорода за пределами купола он существует в широком интервале концентраций как пересыщенный твёрдый раствор водорода в никеле, который некорректно интерпретируют как гидрид никеля.